2011
DOI: 10.1371/journal.pntd.0000967
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and Viral Determinants of Dengue Severity in Hospitalized Adults in Ha Noi, Viet Nam

Abstract: BackgroundThe relationships between the infecting dengue serotype, primary and secondary infection, viremia and dengue severity remain unclear. This cross-sectional study examined these interactions in adult patients hospitalized with dengue in Ha Noi.Methods and Findings158 patients were enrolled between September 16 and November 11, 2008. Quantitative RT-PCR, serology and NS1 detection were used to confirm dengue infection, determine the serotype and plasma viral RNA concentration, and categorize infections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
65
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 44 publications
(71 reference statements)
10
65
1
Order By: Relevance
“…NS1 antigen positive rates were at high levels on days 1-5 and days 6-10. While some investigators found higher detection rates in primary infection as compared to secondary infection, [31][32][33] others found no difference in NS1 detection rates between primary and secondary infection 13,34,35 or higher detection rates in secondary as compared to primary infection. 36 Magnitude and kinetics of NS1 also varied with infecting serotype and viremia clearance.…”
Section: Discussionmentioning
confidence: 95%
“…NS1 antigen positive rates were at high levels on days 1-5 and days 6-10. While some investigators found higher detection rates in primary infection as compared to secondary infection, [31][32][33] others found no difference in NS1 detection rates between primary and secondary infection 13,34,35 or higher detection rates in secondary as compared to primary infection. 36 Magnitude and kinetics of NS1 also varied with infecting serotype and viremia clearance.…”
Section: Discussionmentioning
confidence: 95%
“…Nisalak et al found DENV-3 to be associated with severe outbreaks of dengue in hospitalized cases in Bangkok, Thailand [15]. Fox et al found time to undetectable DENV-2 NS1 protein to be significantly longer than DENV-1 [26]. Extended durations of viremia for DENV-2 and -3 may be the cause of the increased severity of these infections and may be the reason sylvatic DENV-2 is the only serotype to have emerged in Africa from southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans have found that higher peak viremia titers were positively associated with more severe disease [21, 22, 33]; however the evidence for an association between the magnitude and duration of viremia remains inconclusive. Vaughn et al found the time from peak viremia to clearance was more rapid in DHF cases than in DF cases [22], while Fox et al found no difference in rate of clearance between DHF and DF [26]. …”
Section: Discussionmentioning
confidence: 99%
“…In humans, however, the immunopathogenic reaction, rather than the viral load directly (15), is hypothesized to be responsible for the clinical manifestations of severe dengue. Thus, differential triggering of the inflammatory cascade (in particular tumor necrosis factor alpha [TNF-␣] in the ADE mouse model) may explain increased survival in NB-DNJ PERL-treated mice.…”
Section: Discussionmentioning
confidence: 99%